PENINGKATAN PRODUKTIFITAS KOMPOR GAS SATU TUNGKU MELALUI PERBAIKAN TATA LETAK FASILITAS DI PT XYZ - Dany Hermawan (Universitas Mercu Buana, 2017)
Planning facility layout is one effort to organize various equipment and production facilities in order to provide efficiency in terms of layout. Layout problems that occur in PT. XYZ is the length of one-stove gas cooking process, which is caused by several problems of unplanned layout design, displacement activity and irregular material flow, and material handling process is wrong, so the production process of one-stove gas stove becomes old. The purpose of this research is to give layout proposal of layout of production facility and also make regular flow of material so that production process that happened can be more effective and efficient. From this research, we can also recommend the type of conveyance in accordance with the condition of the production area of one-stove gas stove. The steps of redesigning the layout of one furnace gas stove production facility using systematic layout planning (SLP) method, starting with making Operation Process Chart (OPC) and Flow Process Chart (FPC), Multy product Process (MPPC), Sheetable Routing, Activity Releationship Chart (ARC), and Area Releationship Diagram (ARD). The final result of this research is Space Releationship Diagram (SRD), and Block layout of one stove gas production area area along with material flow map based on the layout of the proposal. From the results of data processing and analysis known by the application of the proposed layout of this production capacity can reach 15,840 units/month or an increase of 16.5% from the previous capacity which only reached 13,600 units/month, So as to meet demand demand orders that reached the average 15,250 units/month.